An analysis of methods for gravity determination and their utilization for the calculation of geopotential numbers in the Slovak national levelling network - MAJKRÁKOVÁ, Miroslava; PAPČO, Juraj; ZAHOREC, Pavol; DROŠČÁK, Branislav; MIKUŠKA, Ján; MARUŠIAK, Ivan (Contributions to Geophysics and Geodesy, 2016)
The vertical reference system in the Slovak Republic is realized by the National Levelling Network (NLN). The normal heights according to Molodensky have been introduced as reference heights in the NLN in 1957. Since then, the gravity correction, which is necessary to determine the reference heights in the NLN, has been obtained by an interpolation either from the simple or complete Bouguer anomalies. We refer to this method as the “original”. Currently, the method based on geopotential numbers is the preferred way to unify the European levelling networks. The core of this article is an analysis of different ways to the gravity determination and their application for the calculation of geopotential numbers at the points of the NLN. The first method is based on the calculation of gravity at levelling points from the interpolated values of the complete Bouguer anomaly using the CBA2G SK software. The second method is based on the global geopotential model EGM2008 improved by the Residual Terrain Model (RTM) approach. The calculated gravity is used to determine the normal heights according to Molodensky along parts of the levelling lines around the EVRF2007 datum point EH-V. Pitelov´a (UELN- 1905325) and the levelling line of the 2nd order NLN to Kráľova hoľa Mountain (the highest point measured by levelling). The results from our analysis illustrate that the method based on the interpolated value of gravity is a better method for gravity determination when we do not know the measured gravity. It was shown that this method is suitable for the determination of geopotential numbers and reference heights in the Slovak national levelling network at the points in which the gravity is not observed directly. We also demonstrated the necessity of using the precise RTM for the refinement of the results derived solely from the EGM2008.